Companion diagnostics (CDx) in precision medicine - Kim, Il-Jin (Singapore : Pan Stanford Publishing, 2019)
There is a new trend in anti-cancer therapeutics development: a targeted therapy and precision medicine that targets a subgroup of patients with specific biomarkers. An in vitro diagnostic (IVD) assay is required to identify a subgroup of cancer patients who would benefit from the targeted therapy, or not likely benefit, or have a high risk of side effects from the specific drug treatment. This IVD or medical device is called a companion diagnostic (CDx) assay. It is key to have a robust CDx assay or device for the success of targeted therapy and precision medicine. This book covers the technical, historical, clinical, and regulatory aspects of CDx in precision medicine. Clearly, more and more newly developed oncology drugs will require accompanying CDx assays, and this book, with chapters contributed by renowned oncologists, provides a comprehensive foundation for the knowledge and application of CDx for precision medicine.
4.2 Technology Requirements for Precision Diagnostic Medical Devices4.3 Biomarker Multiplexing Provides Higher Diagnostic Accuracies; 4.4 Regulatory Considerations; 4.4.1 The US; 4.4.2 The EU; 4.4.3 China; 4.5 Other Prerequisites to the Successful Release of Protein Biomarker Signatures for Precision Diagnostics; 4.5.1 AssayWorkflow, Turnaround Time, and Hands-On Time; 4.5.2 Assay Reimbursement and Inclusion in National Guidelines; 4.6 Future Perspectives; 5: Next-Generation Sequencing (NGS) for Companion Diagnostics (CDx) and Precision Medicine; 5.1 Introduction
OCLC-licensed vendor bibliographic record.
Keywords: Cancer -- Treatment; Personalized medicine; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; COMPUTERS / Bioinformatics; MEDICAL / Biotechnology; MEDICAL / Genetics